2020
DOI: 10.1002/cam4.3694
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of gut microbiome in cancer immunotherapy: A novel paradigm for blockade of immune checkpoint inhibitors

Abstract: The human gut microbiome is composed of a complex community of microbes, approximately 10 13-10 14 cells, which plays critical task in disease and health status. 1 The intestinal microbiota consists of different microorganism types including archaea, bacteria, viruses, fungi, and protozoa that live on and inside various humans' organs. 2,3 Different physiological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 134 publications
0
32
0
Order By: Relevance
“…Our reporting of an association between the gut microbiome and immunotherapy outcomes and irAEs in advanced cancer patients is consistent with the results of previous studies [ 29 , 30 , 31 ]. Several studies examining the relationships between the diversity and composition of the gut microbiome and AEs and clinical response during chemotherapy [ 29 ], radiotherapy [ 32 ] and immunotherapy [ 33 ], identified that dysbiosis of the microbiome was related to AEs and clinical response to cancer therapies. These studies suggested that the gut microbiome prior to cancer treatment can be used as a predictor of clinical response and AEs and recommended that assessment of the microbiome in cancer therapy could improve patient care [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our reporting of an association between the gut microbiome and immunotherapy outcomes and irAEs in advanced cancer patients is consistent with the results of previous studies [ 29 , 30 , 31 ]. Several studies examining the relationships between the diversity and composition of the gut microbiome and AEs and clinical response during chemotherapy [ 29 ], radiotherapy [ 32 ] and immunotherapy [ 33 ], identified that dysbiosis of the microbiome was related to AEs and clinical response to cancer therapies. These studies suggested that the gut microbiome prior to cancer treatment can be used as a predictor of clinical response and AEs and recommended that assessment of the microbiome in cancer therapy could improve patient care [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current review is significant in that it included only clinical studies in order to provide updated meaningful evidence for clinicians, cancer patients and carers, whereas previous reviews, examining both animal models and clinical studies in order to elucidate the role of gut microbiota in ICIs, resulted in gaps in their application to real-world clinical practice [ 33 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immune response in cancer therapy was improved by the inhibition of regulatory T cells (Tregs) through Bifidobacterium adolescentis , Enterococcus faecium, Collinsella aerofaciens and Parabacteroides merdae [ 74 ]. The gut microbiota has been shown to increase the efficacy of blockade therapy of programmed cell death 1 (PD-1) protein and its ligand, programmed cell death ligand 1 (PD-L1) [ 80 ]. On the contrary, the anticancer immune response increased and the tumor burden was reduced by depletion of the gut microbiota through oral gavage antibiotics treatment in a mouse model of PC [ 81 ].…”
Section: The Microbiota and Drug Response In Pcmentioning
confidence: 99%
“…However, their mechanisms in enhancing or attenuating the efficacy of immunotherapies need to be identified. Through fecal microbiota transplant (FMT) or supplementation with certain prebiotics, probiotics, or antibiotics, the gut microbial composition could be manipulated to enhance host anticancer immunity and combat drug resistance [ 80 ]. Moreover, the gut microbiota could be used as a biomarker for drug efficacy, treatment response and drug side effects [ 74 ].…”
Section: The Microbiota and Drug Response In Pcmentioning
confidence: 99%
“…Immunotherapy with checkpoint inhibitors, including CTLA-4 and PD-1 inhibitors, are recent additions to the armament of medical oncologists, and have shown impressive responses in people with tumors non-responsive to traditional cytotoxic chemotherapy 52 . These agents favor antitumor T-cell proliferation and stimulation of the immune system partially via depletion of Regulatory T (TReg) cells, which can inhibit normal immune function.…”
Section: The Microbiome and Cancer Treatmentmentioning
confidence: 99%